2019
DOI: 10.1039/c8tc06332j
|View full text |Cite
|
Sign up to set email alerts
|

The difference in electronic structure of MAPI and MASI perovskites and its effect on the interface alignment to the HTMs spiro-MeOTAD and CuI

Abstract: We have studied the electronic structure of CH3NH3PbI3 (MAPI) and CH3NH3SnI3 (MASI) perovskite films by performing X-ray photoelectron spectroscopy (XPS) measurements on in situ grown perovskite films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 53 publications
2
32
0
Order By: Relevance
“…Therefore, the full photovoltage of the classical architecture device has been identified at the back contact (n‐MAPI/p‐spiro‐MeOTAD/Au), which was already predicted in an earlier study, where the energy band diagram between MAPI and spiro‐MeOTAD was investigated. [ 48 ] It is concluded that the classical architecture is an n + ‐SnO 2 /n‐MAPI/p‐spiro‐MeOTAD structure and not an n‐SnO 2 /i‐MAPI/p‐spiro‐MeOTAD structure as it is often referred to in literature. [ 15–17,19 ] In case of an n‐i‐p structure, the photovoltage would be split up between the SnO 2 /MAPI and the MAPI/spiro‐MeOTAD interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the full photovoltage of the classical architecture device has been identified at the back contact (n‐MAPI/p‐spiro‐MeOTAD/Au), which was already predicted in an earlier study, where the energy band diagram between MAPI and spiro‐MeOTAD was investigated. [ 48 ] It is concluded that the classical architecture is an n + ‐SnO 2 /n‐MAPI/p‐spiro‐MeOTAD structure and not an n‐SnO 2 /i‐MAPI/p‐spiro‐MeOTAD structure as it is often referred to in literature. [ 15–17,19 ] In case of an n‐i‐p structure, the photovoltage would be split up between the SnO 2 /MAPI and the MAPI/spiro‐MeOTAD interface.…”
Section: Resultsmentioning
confidence: 99%
“…With the VBM of SnO 2 (VBMSnO2 = 3.85 eV, see Figure S8a, Supporting Information) and MAPI (VBM MAPI = 1.35 eV, see Figure 2c), an offset of 2.32 eV between the VBM of MAPI and SnO 2 results (Δ E VB ), demonstrating an efficient blocking of holes. With the bandgaps of SnO 2 (Eg,SnO2 = 3.60 eV) [ 49 ] and MAPI ( E g,MAPI = 1.58 eV), [ 48 ] the CBM of SnO 2 is positioned below the CBM of MAPI, which will allow electrons to be extracted from MAPI into the SnO 2 layer. Given the SPV of 0.80 eV at the MAPI/spiro‐MeOTAD interface, it is concluded that a built‐in potential of at least 0.80 eV exists at this interface for the dark case.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the performance of devices based on lead halide perovskite is strongly driven by the design of interfaces. [22][23][24] . Here we combine photoemission and (photo)transport measurement to demonstrate that the Fermi level of this material is located deeply within the band gap and that trap plays a limited role on charge recombination.…”
Section: Introductionmentioning
confidence: 99%
“…The measurement shows that MASI, produced by this method, is a p‐type material with valence band maximum (VBM) ‐ E F of 0.4 eV, having a bandgap of 1.3 eV (Figure ). Using a work function Φ of 4.75 eV for ultra‐high vacuum (UHV) deposited MASI, a band diagram can be drawn as displayed in Figure , which may be used for the first selection of appropriate hole and electron extraction layers according to the simple vacuum level alignment.…”
Section: Resultsmentioning
confidence: 99%
“…III (Figure ); Right, concluded band diagram. The value of the bandgap E g is taken from our UV–vis measurement Figure and for the work function Φ, marked with an asterisk (*), from our measurement …”
Section: Resultsmentioning
confidence: 99%